H5P Based Learning Media to Reinforce Pre-Service Science Teachers’ Critical Thinking Skills: Development and Validation - Dhita Ayu Permata Sari; Wahono Widodo; Laily Rosdiana; Dyah Permata Sari; Ernita Vika Aulia (Postgraduate, University of Mataram, 2023)
Student’s critical thinking skills in higher education level should be enhanced using diverse methods, one of which by developing learning media as assistance in conceiving the skills. This study was undertaken to determine the validity of the H5P learning media using ALLR (Activity Based-Lesson Learn-Reflection) model that could be embedded in a Moodle-based learning management system for Basic Science course to reinforce the pre-service science teachers’ critical thinking skills. This study used research and development (R&D) design using 4D development model. The developed learning media was an interactive learning media for Basic Science course that contained the ALLR learning model developed using the H5P platform embedded in Moodle-based SIDIA UNESA learning management system. The media was given to three experts whose expertise were science learning and learning media development. The validation was based on assessment criteria which included content, presentation, and language aspects. The results showd that all the assessment criteria for the learning media developed were declared very valid, except for interactivity sub-criteria which was valid. It can be concluded that H5P-based interactive media in LM with ALLR Learning Model is suitable for improving the critical thinking skills of pre-service science teachers in the Basic Science Course.